Biosynthesis of α-Gal Epitopes (Galα1-3Galβ1-4GlcNAc-R) and Their Unique Potential in Future α-Gal Therapies - Galili, Uri (Frontiers in Molecular Biosciences, 2021)
The α-gal epitope is a carbohydrate antigen which appeared early in mammalian evolution and is synthesized in large amounts by the glycosylation enzyme α1,3galactosyltransferase (α1,3GT) in non-primate mammals, lemurs, and New-World monkeys. Ancestral Old-World monkeys and apes synthesizing α-gal epitopes underwent complete extinction 20–30 million years ago, and their mutated progeny lacking α-gal epitopes survived. Humans, apes, and Old-World monkeys which evolved from the surviving progeny lack α-gal epitopes and produce the natural anti-Gal antibody which binds specifically to α-gal epitopes. Because of this reciprocal distribution of the α-gal epitope and anti-Gal in mammals, transplantation of organs from non-primate mammals (e.g., pig xenografts) into Old-World monkeys or humans results in hyperacute rejection following anti-Gal binding to α-gal epitopes on xenograft cells. The in vivo immunocomplexing between anti-Gal and α-gal epitopes on molecules, pathogens, cells, or nanoparticles may be harnessed for development of novel immunotherapies (referred to as “α-gal therapies”) in various clinical settings because such immune complexes induce several beneficial immune processes. These immune processes include localized activation of the complement system which can destroy pathogens and generate chemotactic peptides that recruit antigen-presenting cells (APCs) such as macrophages and dendritic cells, targeting of antigens presenting α-gal epitopes for extensive uptake by APCs, and activation of recruited macrophages into pro-reparative macrophages. Some of the suggested α-gal therapies associated with these immune processes are as follows: 1. Increasing efficacy of enveloped-virus vaccines by synthesizing α-gal epitopes on vaccinating inactivated viruses, thereby targeting them for extensive uptake by APCs. 2. Conversion of autologous tumors into antitumor vaccines by expression of α-gal epitopes on tumor cell membranes. 3. Accelerating healing of external and internal injuries by α-gal nanoparticles which decrease the healing time and diminish scar formation. 4. Increasing anti-Gal–mediated protection against zoonotic viruses presenting α-gal epitopes and against protozoa, such as Trypanosoma, Leishmania, and Plasmodium, by vaccination for elevating production of the anti-Gal antibody. The efficacy and safety of these therapies were demonstrated in transgenic mice and pigs lacking α-gal epitopes and producing anti-Gal, raising the possibility that these α-gal therapies may be considered for further evaluation in clinical trials.